(untitled) (Bangladesh Journal of Animal Science, 2023)
This study aimed to assess the hematological parameters, productive and reproductive performances of Red Chittagong cows (RCC) under farming and rural production systems. Hence, three villages (Sailabari, Munsumi and Baniagati) of Khokshabari union under Sadar upazila of Sirajganj district were selected. The 40 Red Chittagong cows from each production system were taken under this study. Twenty (20) farmers were selected through direct interviewing process with a structured questionnaire. Farming condition and rural condition data were analyzed with unpaired t-test along with GLM procedure of SAS statistical package. Services per conception (times), postpartum heat period (days) and calving interval (days) had significant (p<0.01) differences between farming and rural condition, whereas, age at first calving (months) significantly differed (p<0.05). Average milk yield (kg/d) had significantly different at the values of p<0.05, whereas, lactation period was significantly differed at the values of p<0.01. Hemoglobin (g /100ml) and PCV% were significantly different (p<0.05) between farming and rural condition of RCC in the selected areas. From the study, it may be concluded that the productive and reproductive performances of RCC were better in farming condition than in rural conditions in selected areas. Bangladesh Journal of Animal Science, 52 (2): 55-60.